MoO2 / K7HNb6O19 n-n junction and preparation method and application thereof
By constructing n-n heterojunction photocatalysts of n-type MoO2 and n-type K7HNb6O19, the problem of low charge separation efficiency of existing photocatalysts is solved, and the efficient photocatalytic hydrogen production effect under alkaline conditions is achieved.
Patent Information
- Application Number
- CN202411435084.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-02-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the process of water decomposition of hydrogen, existing photocatalysts have limited practical applications due to low charge separation efficiency and hindered surface catalytic reactions.
The n-n heterojunction of n-type MoO2 and n-type K7HNb6O19 was successfully constructed by solvothermal method to form a composite photocatalyst with a lamellar flower-like structure.
The photocatalytic hydrogen production activity was significantly improved. Especially under alkaline conditions, the hydrogen production of MON-1.0 samples reached 2358.82 μmol g-1, which was better than the previous K7HNb6O19-based photocatalytic system.
Smart Images

Figure CN119406399A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of photocatalysis technology and specifically relates to MoO 2 / K 7 HkDJ 6 O 19 nn junction and its preparation method and application. Background Art
[0002] As a promising economical alternative energy source, hydrogen energy has attracted extensive attention in the past few decades due to its high energy and environmental friendliness. Among the various hydrogen production methods, one of the most attractive methods is to use semiconductor-based photocatalysts to convert solar energy into hydrogen energy through the water splitting pathway to alleviate the energy crisis and environmental pollution. However, the relatively low charge separation efficiency and insufficient surface catalytic reaction of semiconductors hinder their practical application. In order to significantly improve the photocatalytic performance of catalysts, various strategies have been adopted, such as surface modification, element doping, defect engineering, and the construction of heterojunction composites. Among them, constructing heterojunctions is considered to be a high-quality, efficient and simple strategy.
[0003] Polyoxometalates (POMs) are an attractive class of transition metal oxide clusters. They are ideal photocatalysts due to their tunable band gap structure and special structural characteristics. Their advantages can be summarized as follows: (1) POMs have reversible redox properties and can gradually undergo multi-electron redox reactions without significant structural changes; (2) they have semiconductor-like structural characteristics and tunable electronic properties and energy levels. These advantages make POMs have unique photochemical activity and photostability. Therefore, POMs have been widely used in the field of photocatalysis. Studies have found that among polyoxometalates, due to the Lindqvist-type K 7 HkDJ 6 O 19 It has a high negative charge and strong basicity, is easy to prepare, and has high stability, which is of special significance in photocatalysis. 7 HkDJ 6 O 19 It has n-type semiconductor properties (Heng, S., Li, L., Li, W., Li, H., Pang, J., Zhang, M. et al. Enhanced Photocatalytic Hydrogen Production of the Polyoxoniobate Modified with RGO and PPy. Nanomaterials. 10 (2020) 2449.) and meets the requirements for constructing a nn junction.
[0004] Molybdenum dioxide (MoO2 ) is one of the rutile transition metal oxides, which has good electronic conductivity, low metal resistivity, high melting point and excellent chemical stability, and has attracted widespread attention. In particular, it has good alkali resistance and can form a nn heterojunction with alkaline n-type polyoxometalates to achieve efficient alkaline hydrogen evolution performance. Although there are some studies on MoO 2 Reports on the construction of heterojunctions, such as MoO 2 / Au / Mn 0.5 Cd 0.5 S(Liu,Y.,Wang,L.,Lv,H.,Wu,X.,Xing,X.,Song.S.Constructing robust MoO 2 / Au / Mn 0.5 Cd 0.5 S multiple heterojunctions for improved photocatalytic hydrogen evolution:an insight into the synergetic effect of MoO 2 and Au cocatalysts.Applied Surface Science.541(2021)148582.), MoO 2 / Zn 0.5 Cd 0.5 S(Du,H.,Xie,X.,Zhu,Q.,Lin,L.,Jiang,Y.,Yang,Z.,et al.Metallic MoO 2 cocatalyst significantly enhances visible-light photocatalytic hydrogenproduction over MoO 2 / Zn 0.5 Cd 0.5 S heterojunction.Nanoscale.7(2015)5752.) and MoO 2 / gC 3 N 4 (Ji, H., Fei, T., Zhang, L., Yan, J., Fan, Y., Huang, J., et al. Synergistic effects of MoO 2 nanosheets and graphene-like C 3 N 4for highly improved visible light photocatalytic activities. Applied Surface Science. 457 (2018) 1142-1150.), but there is no report on combining n-type polyoxometalates with semiconductor properties with n-type MoO 2 Combined with reports on the construction of nn junctions, and currently on MoO 2 There are also few reports on its use as a photocatalyst. Summary of the invention
[0005] The present invention uses a simple solvothermal method to synthesize n-type MoO 2 With n-type K 7 HkDJ 6 O 19 The coupling successfully constructed a n-n junction, which is the first example of a POMn-n junction. 2 or K 7 HkDJ 6 O 19 Two pure components, MoO 2 / K 7 HkDJ 6 O 19 The photocatalytic hydrogen production activity of the nn junction was significantly improved. In particular, the optimal MON-1.0 sample showed good alkaline hydrogen production activity at pH = 8.8, reaching 2358.82 μmol g -1 , which is better than the previously reported K 7 HkDJ 6 O 19 Hydrogen evolution performance of the photocatalytic system.
[0006] The present invention first provides a MoO 2 / K 7 HkDJ 6 O 19 nn junction, the MoO 2 / K 7 HkDJ 6 O 19 The nn junction has a lamellar flower-like structure, which is composed of MoO 2 and K 7 HkDJ 6 O 19 The nn heterojunction formed by solvothermal reaction coupling, the MoO 2 and K 7 HkDJ 6 O 19 The mass ratio is 1:(5~30).
[0007] As a preferred solution, the MoO 2 and K 7 HkDJ 6 O 19 The mass ratio is 1:25.
[0008] The present invention also provides MoO 2 / K 7 HkDJ 6 O 19 The preparation method of the nn junction comprises the following contents:
[0009] (1) Synthesizing K using existing technology 7 HkDJ 6 O 19 ;MoO 2 It can also be synthesized using existing technology, or using commercially available MoO 2 ;
[0010] (2) Add MoO to a mixed solvent of methanol and water 2 and K 7 HkDJ 6 O 19 , the MoO 2 and K 7 HkDJ 6 O 19 The mass ratio of is 1:(5-30), ultrasonic treatment is for more uniform mixing, constant temperature reaction at 140°C-180°C for 8-24h, cooling, washing and drying to obtain.
[0011] The volume ratio of methanol to water is 1:1, the ultrasonic treatment is performed for 1.5 h, and the drying is performed at 60° C. under vacuum for 12 h.
[0012] The present invention also provides the above-mentioned MoO 2 / K 7 HkDJ 6 O 19 The application of nn junction as a photocatalyst in photocatalytic hydrogen production. Specifically, under light conditions, the photocatalyst and sacrificial agent are added to water to photolyze water to obtain hydrogen.
[0013] In a further embodiment, the mass ratio of the photocatalyst to water is 5:4, the volume ratio of water to the sacrificial agent is 4:1, the sacrificial agent is methanol, ethanol, triethanolamine or isopropanol, and the sacrificial agent is preferably methanol; in addition, the reaction time of the entire photocatalytic hydrogen production is 5 hours. The photocatalytic hydrogen production reaction can be carried out at a pH value of 6 to 11, wherein the photocatalyst of the present invention has a high hydrogen production activity under alkaline conditions, especially under pH = 8.8.
[0014] The beneficial effects of the present invention are:
[0015] The present invention successfully prepared a MoO with a lamellar flower-like structure by a simple solvothermal method. 2 / K 7 HkDJ 6 O 19 nn heterojunction photocatalyst, photocatalytic experiments show that compared with pure MoO 2 or K 7 HkDJ 6 O 19 In comparison, the composite photocatalyst showed excellent performance, with the highest hydrogen production reaching 2358.82 μmol g -1 , than pure K 7 HkDJ 6 O 19 The present invention also explains the reaction mechanism, MoO 2 and K 7 HkDJ 6 O 19 The formed nn heterojunction and lamellar flower-like structure can effectively transfer and separate photogenerated electrons and holes, which is beneficial to the photocatalytic hydrogen production reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 (a)K 7 HkDJ 6 O 19 、MoO 2 and MON-X hydrogen production activity; (b) K 7 HkDJ 6 O 19 、MoO 2 and hydrogen production rates of MON-X; (c) hydrogen production performance of MON-1.0 photocatalyst in the presence of different sacrificial agents; (d) hydrogen production performance of MON-1.0 under different pH conditions; (e) stability test of MON-1.0; (f) XRD spectra of MON-1.0 before and after reaction.
[0017] Figure 2 K 7 HkDJ 6 O 19 、MoO 2 And XRD spectra of MON-X.
[0018] Figure 3 (a~c)K 7 HkDJ 6 O 19 、MoO 2 and SEM images of MON-1.0; (d) elemental mapping image of MON-1.0 composite material.
[0019] Figure 4 (a) XPS full spectrum of MON-1.0; XPS high-resolution spectrum (b) Nb 3d; (c) Mo 3d; (d) O1s.
[0020] Figure 5 Pure K 7 HkDJ 6 O 19 、MoO 2 and nitrogen adsorption-desorption isotherms of MON-1.0.
[0021] Figure 6 (a)K 7 HkDJ 6 O 19 、MoO 2 UV-Vis DRS spectra of and MON-X; (b~d) K 7 HkDJ 6 O 19 、MoO 2 and the bandgap width of MON-1.0.
[0022] Figure 7 (a)K 7 HkDJ 6 O 19 、MoO 2 and transient photocurrent responses of MON-1.0; (b) electrochemical impedance spectroscopy (EIS); (c) PL spectrum.
[0023] Figure 8 (a, b) K 7 HkDJ 6 O 19 、MoO 2 Mott-Schottcky plot; (c) MoO 2 / K 7 HkDJ 6 O 19 Diagram of the photocatalytic mechanism under light irradiation. DETAILED DESCRIPTION
[0024] The present invention is described in more detail below through specific implementation modes to facilitate understanding of the technical solution of the present invention, but is not intended to limit the protection scope of the present invention.
[0025] Example 1
[0026] The materials used in this embodiment include: niobium pentoxide (Nb 2 O 5 , AR), potassium hydroxide (KOH, AR), molybdenum powder (Mo, AR), molybdenum trioxide (MoO 3, AR), ethanol (EtOH, AR), methanol (MeOH, AR), triethanolamine, isopropanol, all reagents and solvents were of analytical grade and commercially available.
[0027] 1. Experimental process
[0028] 1.1K 7 HkDJ 6 O 19 Synthesis
[0029] According to the reports in the literature (Filowitz, M., Ho, RKC., Klemperer, WG., Shum, W. 17 O nuclearmagnetic resonance spectroscopy of polyoxometalates.1.Sensitivity and resolution.Inorganic Chemistry.18(1979)93-103.), first 13.3g Nb 2 O 5 and 26g KOH were added to a nickel crucible and mixed evenly, and then the mixture was heated at 480°C for 50 minutes, cooled to room temperature and dissolved in 100mL of water, and when the water was evaporated to make the solution volume reach about 50mL, the mixture was filtered and placed at 0°C for 12 hours to form needle-shaped crystals. It was then washed with a mixed solvent of water and anhydrous ethanol in a ratio of 1:1 (V / V) and vacuum dried to obtain a white solid.
[0030] 1.2 Synthesis of MON-X photocatalyst
[0031] MoO 2 According to previous reports (Liu, Y., Wang, L., Lv, H., Wu, X., Xing, X., Song, S.Constructing robust MoO 2 / Au / Mn 0.5 Cd 0.5 S multiple heterojunctions for improved photocatalytic hydrogen evolution:an insight into the synergetic effect ofMoO 2 and Au cocatalysts.Applied Surface Science.541(2021)148582.) were synthesized by a hydrothermal method. Specifically, molybdenum powder (0.5 mmol) and MoO 3(1 mmol) was mixed with deionized water (40 mL) to form a suspension. After stirring for 1 hour, NH 4 Cl (100 mg) was slowly added to the suspension and kept stirring for 2 hours. The mixture was then transferred to a 50 mL autoclave and treated at 200 ° C for 15 hours. After cooling to room temperature, the black precipitate was collected, washed with distilled water and ethanol, and finally dried in vacuum at 60 ° C for 12 hours.
[0032] In a 20 mL mixed solvent of high purity water and methanol (1:1 (V / V), 0.04 g of the prepared MoO 2 and K 7 HkDJ 6 O 19 (0.2, 0.4, 0.6, 0.8, 1.0, 1.2 g). After mixing, stir and ultrasonically treat for 1.5 h, transfer to a 30 mL high pressure reactor, keep constant temperature at 160 ° C for 12 h, cool naturally to room temperature, and wash with high purity water and anhydrous ethanol by centrifugation for 3 times. Then vacuum dry at 60 ° C for 12 h. For the convenience of description, the final product is marked as MON-X (X = 0.2, 0.4, 0.6, 0.8, 1.0, 1.2).
[0033] 1.3 Product analysis
[0034] The crystal structure of the prepared MON-X was analyzed by X-ray diffractometer (XRD, Bruker D8 advanced diffractometer, Germany). The morphology of the samples was observed by field emission scanning electron microscope (FESEM, JSM-7610F, Japan) and high resolution transmission electron microscope (HRTEM, JEM-F200, Japan). The surface electronic state of the samples was detected by X-ray photoelectron spectroscopy (XPS, ESCALAB 250xi, USA). BaSO 4 The UV-visible diffuse reflectance spectrum of MON-X was measured at room temperature using a UV-visible spectrophotometer (Agilent Cary 5000, USA) with 10% NH 2 O as reference. The specific surface area and pore size distribution of the sample MON-X were calculated using the Brunauer-Emmett-Teller (BET, BELSORP-Max II, Japan) method on the nitrogen adsorption-desorption isotherm. The photoluminescence spectrum (PL) was measured on a spectrophotometer (F7000, Japan) with an excitation wavelength of 430 nm.
[0035] 1.4 Photocatalytic hydrogen production
[0036] Photocatalytic water splitting to produce H in a quartz reactor using argon as carrier gas 2The reaction system was maintained at 6°C by circulating cooling water. The reaction system consisted of a photocatalyst (MON-X, 50 mg), high-purity water (40 mL) and CH 3 OH (10 mL). The light source was a 300 W Xe lamp (CEL-HXF300, Beijing, China). The gas products were analyzed every hour using the CEL-PAEM-D6 online detection system (CEL-PAEM-D6, Beijing, China).
[0037] 1.5 Photoelectrochemical test
[0038] All electrochemical experiments were performed on an electrochemical workstation with a standard three-electrode system (CHI-660, Shanghai, China). A platinum electrode, a saturated calomel electrode (SCE), and FTO coated with MON-X composites were used as the counter electrode, reference electrode, and working electrode, respectively. 2 SO 4 Aqueous solution was used as auxiliary electrolyte. High purity N 2 Deoxygenate for at least 20 minutes.
[0039] 2. Results
[0040] 2.1 Photocatalytic hydrogen production activity
[0041] The photocatalytic hydrogen evolution performance of the obtained sample MON-X was evaluated in an alkaline solution (pH = 9.8) with methanol as sacrificial agent (methanol concentration of 20%, V / V) under the irradiation of a 300W xenon lamp. 7 HkDJ 6 O 19 、MoO 2 In comparison, all prepared MON-X exhibited excellent photocatalytic hydrogen evolution performance ( Figure 1 a). As K 7 HkDJ 6 O 19 As the content of K increases, the hydrogen production activity gradually increases. 7 HkDJ 6 O 19 When the addition amount is 1.0 g, the maximum hydrogen production rate of MON-1.0 can reach 2189.37 μmol g within 5 h. -1 ( Figure 1 a), the hydrogen production rate is 471.76 μmol h -1 g -1 ( Figure 1 b).
[0042] In order to study the effects of different sacrificial agents on hydrogen production performance and explore the appropriate pH value, a series of control experiments were conducted using the MON-1.0 sample as an example (ethanol, methanol, triethanolamine, and isopropanol were selected as sacrificial agents under the condition of pH 9.8; under the condition of fixed methanol as the sacrificial agent, the experimental conditions of pH = 6.8, 7.8, 8.8, 9.8, and 10.8 were used). It can be seen that Figure 1 In c, under the same pH conditions, when methanol is used as the sacrificial agent, the catalyst has the best hydrogen production performance, indicating that methanol is the best sacrificial agent for hydrogen release, followed by ethanol, triethanolamine, and isopropanol. Figure 1 d It can be seen that when methanol is used as the sacrificial agent, the increase in pH value significantly enhances the photocatalytic hydrogen production activity of MON-1.0. The highest hydrogen production is achieved at pH = 8.8, reaching 2358.82 μmol g -1 , achieving the optimization of hydrogen production under alkaline conditions.
[0043] In summary, the MON-X composite catalyst prepared in this example obtained good hydrogen production activity under alkaline conditions, which is better than most POM-based photocatalysts (Gao, X., Wang, J., Xue, Q., Ma, Y., Gao, Y. AgBr / Polyoxometalate / Graphene oxide ternary composites for visible light-driven photocatalytic hydrogen production. ACS Applied Nano Materials. 4 (2021) 2126-2135, Matt, B., Fize, J., Moussa, J., Amouri, H., Pereira, A., Artero, V., et al. Charge photo-accumulation and photocatalytic hydrogen evolution under visible light at an iridium(III)-photosensitized polyoxotungstate. Energy&Environmental Science. 6 (2013) 1504.).
[0044] Since the stability of the catalyst plays a vital role in its practical application. Finally, the MON-1.0 sample with the best activity was used as a representative to conduct a hydrogen evolution cycle test. The experimental conditions were the same as those of the photocatalytic hydrogen production activity experiment. The difference was that the system was evacuated after one photocatalytic hydrogen production cycle before the next photocatalytic hydrogen production cycle was carried out. Figure 1e It can be seen that after 4 consecutive reaction cycles under UV-vis irradiation, H 2 The yield remained relatively stable, indicating that the prepared sample had good stability. This can be further verified by the almost identical XRD spectra before and after the reaction, such as Figure 1 As shown in Figure f, the XRD pattern of MON-1.0 did not change significantly before and after 4 cycles, indicating that MON-1.0 has good stability.
[0045] 2.2 XRD analysis
[0046] X-ray diffraction (XRD) was used to characterize the structure and phase composition of the catalyst. Figure 2 As shown, the MoO prepared by solvothermal synthesis in this embodiment 2 The characteristic peaks of the standard card (JCPDS No.02-0422) match well, among which the diffraction peaks at 25.9°, 37.0°, 53.6°, 60.6° and 67.6° correspond to MoO 2 (011), (211), (220), (013) and (204) crystal planes. 7 HkDJ 6 O 19 The characteristic peaks of K are 9.7°, 26.0°, and 48.0° respectively. For the MON-X composite photocatalyst, K 7 HkDJ 6 O 19 and MoO 2 The characteristic diffraction peaks ( Figure 2 ), no other new diffraction peaks appeared, proving the successful preparation of MON-X composite materials.
[0047] 2.3 SEM and TEM analysis
[0048] The K 7 HkDJ 6 O 19 、MoO 2 The surface morphology of MON-1.0 was studied. Figure 3 (a~c) are shown. The figure clearly shows that pure K 7 HkDJ 6 O 19 It is rod-shaped, pure MoO 2 Agglomerated particles with no regular geometric shape. Figure 3 In c, the composite material MON-1.0 shows a petal-like shape. In addition, the element distribution of MON-1.0 is also studied in this embodiment. Figure 3 As shown in Figure d, the elements K, Nb, Mo, and O are uniformly distributed in the MON-1.0 composite material.2 and K 7 HkDJ 6 O 19 In the composite material, they coexist and are in close contact, which is beneficial for electron transfer between the two materials.
[0049] 2.4XPS analysis
[0050] X-ray photoelectron spectroscopy (XPS) was used to characterize the K 7 HkDJ 6 O 19 、MoO 2 The surface chemical states of MON-1.0 were determined and studied. Figure 4 As shown in a, the full XPS spectrum of MON-1.0 shows the presence of K, Nb, Mo and O, which is consistent with the results of elemental mapping, proving the successful preparation of the MON-1.0 composite material. Figure 4 b is the XPS spectrum of Nb3d. The binding energies of 206.2eV and 209.0eV in MON-1.0 are Nb3d 5 / 2 and Nb 3d 3 / 2 , indicating that Nb 5+ (highest oxidation state). 7 HkDJ 6 O 19 In comparison, the peak of Nb3d shifts to a higher binding energy by 0.3 eV, which may be due to the K 7 HkDJ 6 O 19 with MoO 2 caused by the strong interaction between them.
[0051] In order to further identify the chemical state of the Mo element, pure MoO 2 The Mo 3dXPS spectrum, such as Figure 4 As shown in c, three valence states of Mo can be observed, namely Mo 4+ 、Mo 6+ and Mo 0 .Mo 6+ The oxidation state of MoO may be due to the storage of the sample. 2 The metal Mo may be related to the small amount of molybdenum powder remaining in the synthesis process. According to previous studies, the presence of metal Mo can effectively promote the catalyst's ability to capture photogenerated electrons and reduce the charge transfer resistance, thereby effectively promoting H 2 Producing activity (Liu, Y., Wu, H., Lv, H., Wu, X. Strategic integration of MoO 2 onto Mn 0.5 Cd0.5 S / Cu 2 O pn junction: Rational design with efficient chargetransfer for boosting photocatalytic hydrogen production. PowderTechnology. 394 (2021) 171–180.). Figure 4 d is the high-resolution spectrum of O1s. For pure MoO 2 The peaks at 529.5eV and 530.9eV are attributed to lattice oxygen and -OH groups adsorbed on the surface. In the composite MON-1.0, the energy band at 529.3eV belongs to lattice oxygen, and the peak at 531.0eV belongs to -OH groups adsorbed on the surface. XPS analysis results show that MoO 2 Has successfully cooperated with K 7 HkDJ 6 O 19 This tight coupling helps speed up the transfer of electrons between the two.
[0052] 2.5BET Analysis
[0053] The nitrogen adsorption-desorption experiment was used to investigate the 7 HkDJ 6 O 19 、MoO 2 The specific surface area, pore size distribution and pore volume of MON-1.0 composite materials. Figure 5 As shown, K 7 HkDJ 6 O 19 、MoO 2 and MON-1.0 composite materials 2 The adsorption-desorption isotherm shows a typical IV isotherm and H3 type hysteresis loop, indicating that the photocatalyst prepared in this example has a mesoporous structure. 7 HkDJ 6 O 19 and MoO 2 Compared with the MON-1.0 composite material, the specific surface area, average pore size and pore volume of the MON-1.0 composite material increased significantly. The mesoporous structure and large specific surface area of MON-1.0 are conducive to providing abundant active sites, promoting the adsorption of the catalyst on the reactant molecules and improving the photocatalytic performance.
[0054] Table 1. Pure K 7 HkDJ 6 O 19 、MoO 2 and the specific surface area (S BET), pore volume (V p ) and aperture (D p ).
[0055] sample <![CDATA[S BET (m 2 g -1 ) a ]]> <![CDATA[V p (cm 3 g -1 ) b ]]> <![CDATA[D p (nm)]]> <![CDATA[K 7 HNb 6 HE 19 ]]> 5.9 0.013 9.01 <![CDATA[MoO 2 ]]> 12.7 0.086 26.91 MON-1.0 23.2 0.174 29.99
[0056] In Table 1, a Denotes that the ions were obtained by the BET method.
[0057] b Indicates relative pressure (p / p 0 ) is 0.99 when N 2 The adsorption volume is the total pore volume.
[0058] 2.6 UV-Vis DRS analysis
[0059] In order to study the light absorption ability of the catalyst, K 7 HkDJ 6 O 19 、MoO 2 and the UV-visible diffuse reflectance spectra of MON-1.0, such as Figure 6 a. K 7 HkDJ 6 O 19 It has strong absorption in the ultraviolet region, and the absorption band edge is about 302nm. 2 It shows strong absorption in the range of 200-800nm, indicating that MoO 2 It has strong UV-visible absorption ability. 7 HkDJ 6 O 19 In comparison, the absorption band edges of all composites showed an obvious red shift, which is due to the MoO 2 Contribution of Figure 6 (b~d), K 7 HkDJ 6 O 19 、MoO 2 The band gap values of MoO and MON-1.0 are 4.24 eV, 1.16 eV and 3.75 eV respectively. 2 After the introduction, the band gap of the obtained composite material becomes smaller, which means that the MON-1.0 composite material is more likely to produce photoelectric transition effect and has a higher solar energy utilization rate. This is consistent with the enhanced photocatalytic performance of the MON-1.0 composite material.
[0060] 2.7 Electrochemical characterization and fluorescence spectroscopy analysis
[0061] The electron-hole separation efficiency of the catalyst was further studied through photoelectric performance tests, which is crucial to the photocatalytic activity of the catalyst. Figure 7 It can be seen from the transient photocurrent response of pure K7 HkDJ 6 O 19 The photocurrent density is relatively low due to the rapid recombination of charge carriers. 2 After the material was added, the photocurrent density of MON-1.0 was significantly improved. Generally, a stronger photocurrent density means more efficient charge transfer and separation efficiency, which is helpful for the subsequent photoreaction process. Figure 7 The electrochemical impedance spectroscopy of b gives similar results. MON-1.0 shows a smaller arc radius, which means a smaller charge transfer impedance and a higher carrier transfer efficiency. Figure 7 c, and the original K 7 HkDJ 6 O 19 In comparison, the PL emission intensity of MON-1.0 is the lowest, indicating that the introduction of MoO 2 It is beneficial to reduce the carrier recombination rate. These results are consistent with the excellent photocatalytic performance of MON-1.0.
[0062] 2.8MoO 2 / K 7 HkDJ 6 O 19 Study on the mechanism of photocatalysis
[0063] To further evaluate the MoO 2 / K 7 HkDJ 6 O 19 The mechanism of the improvement of heterojunction photocatalytic activity was studied by using the Mott-Schottky method to determine K 7 HkDJ 6 O 19 and MoO 2 The band structure of the sample. Figure 8 It can be clearly observed in a and b that K 7 HkDJ 6 O 19 and MoO 2 The MS curves all show a positive slope, indicating that K 7 HkDJ 6 O 19 and MoO 2 is an n-type semiconductor. By extrapolating the graph to 1 / C 2 = 0, the flat band potentials of the samples are -0.61 and -0.1 V respectively relative to the saturated calomel electrode (SCE), which are converted to -0.37 and 0.14 V respectively relative to the standard hydrogen electrode (NHE). fb It is about 0.2eV lower than the conduction band (CB) of n-type semiconductors and about 0.2eV higher than the valence band (VB) of p-type semiconductors. Therefore, K7 HkDJ 6 O 19 and MoO 2 E CB are -0.57 and -0.06 eV respectively. VB =E CB +E g , K 7 HkDJ 6 O 19 and MoO 2 E VB can be calculated to be +3.67eV and +1.10eV, respectively. Based on the above experiments and characterizations, the photocatalytic mechanism can be described in Figure 8 c, due to K 7 HkDJ 6 O 19 The Fermi level of MoO 2 When the two semiconductors come into contact with each other, electrons from K 7 HkDJ 6 O 19 Transfer to MoO 2 , positive and negative charges are accumulated in K 7 HkDJ 6 O 19 To MoO 2 The transfer of electrons continues until their Fermi levels reach equilibrium, resulting in K 7 HkDJ 6 O 19 and MoO 2 An internal electric field is formed at the interface. Under light conditions, K 7 HkDJ 6 O 19 and MoO 2 The formation of the nn heterojunction and the influence of the internal electric field generated on both sides cause electrons to flow from MoO 2 CB to K 7 HkDJ 6 O 19 The holes migrate from K 7 HkDJ 6 O 19 VB transferred to MoO 2 VB, thereby preventing the rapid recombination of electron holes. Photogenerated electrons will gather in nK 7 HkDJ 6 O 19 On the CB, place H 2 O dissociated H + Reduction to H 2 At the same time, holes in n-type MoO 2The VB will be consumed by the sacrificial agent. The improvement of hydrogen production performance is due to the formation of a new nn heterojunction, which improves the separation efficiency of photoexcited carriers.
[0064] In summary, this paper synthesized a new type of layered MoO for the first time via a simple solvothermal reaction. 2 / K 7 HkDJ 6 O 19 nn heterojunction photocatalyst. K 7 HkDJ 6 O 19 The introduction of MoO 2 Aggregation of nanoparticles. The study found that the prepared composites all have good alkaline hydrogen evolution performance. Among them, MON-1.0 showed the best hydrogen production activity when methanol was used as the sacrificial agent and the pH value was 8.8. The excellent hydrogen production activity comes from MoO 2 and K 7 HkDJ 6 O 19 The built-in electric field generated by the coupled nn heterojunction accelerates the separation of photoinduced electron-hole pairs, which can be further demonstrated by photoelectrochemical tests and PL results. In addition, the prepared composite also has good stability in photocatalytic hydrogen production. The present invention not only achieves efficient photocatalytic hydrogen production under alkaline conditions, but also provides a feasible design strategy for constructing nn junction composite materials, and also broadens the application of n-type POM in energy conversion using solar energy.
[0065] The embodiments described above are only preferred embodiments of the present invention and are not intended to limit the scope of implementation of the present invention. Therefore, any equivalent changes or modifications made according to the structures, features and principles described in the patent scope of the present invention should be included in the scope of the patent application of the present invention.
Claims
1. MoO2 / K7HNb6O 19 nn junction, characterized in that The MoO2 / K7HNb6O 19 nn junction has a lamellar flower-like structure, the MoO2 / K7HNb6O 19 The nn junction is made of MoO2 and K7HNb6O 19 The nn heterojunction formed by solvothermal coupling reaction, the MoO2 and K7HNb6O 19 The mass ratio is 1:(5~30).
2. MoO2 / K7HNb6O according to claim 1 19 nn junction, characterized in that The MoO2 and K7HNb6O 19 The mass ratio is 1:
25.
3. MoO2 / K7HNb6O 19 The method for preparing a nn junction is characterized in that: Includes the following: (1) Synthesis of K7HNb6O 19 ; (2) Adding MoO2 and K7HNb6O synthesized in step (1) to a mixed solvent of methanol and water 19 , the MoO2 and K7HNb6O 19 The mass ratio of is 1:(5-30), ultrasonic treatment, constant temperature reaction at 140-180°C for 8-24h, cooling, washing and drying to obtain.
4. A MoO2 / K7HNb6O according to claim 3 19 The method for preparing a nn junction is characterized in that: In step (2), the volume ratio of methanol to water is 1:1; and the drying is performed under vacuum at 60° C. for 12 h.
5. MoO2 / K7HNb6O according to any one of claims 1 to 2 19 nn junction, or MoO2 / K7HNb6O prepared by any one of the methods of claims 3 to 4 19 Application of nn junction as photocatalyst in photocatalytic hydrogen production.
6. The use according to claim 5, characterized in that: The photocatalytic hydrogen production specifically comprises: adding a photocatalyst and a sacrificial agent into water under light conditions, and photolyzing water to obtain hydrogen.
7. The use according to claim 6, characterized in that: The mass ratio of the photocatalyst to water is 5:4, and the volume ratio of water to the sacrificial agent is 4:
1.
8. The use according to claim 6, characterized in that: The sacrificial agent is methanol, ethanol, triethanolamine or isopropanol.
9. The use according to claim 6, characterized in that: The photocatalytic hydrogen production is carried out at a pH value of 6-11.
10. The use according to claim 6, characterized in that: The photocatalytic hydrogen production is carried out under alkaline conditions.
Citation Information
Patent Citations
Linquist type K7HNb6O19-polypyrrole-reduced graphene oxide composite photocatalyst as well as preparation method and application thereof
CN109046470A
Preparation method and application of cobalt oxide / potassium niobate p-n heterojunction composite photocatalyst
CN111036224A
Preparation method and application of Mo-doped HNb3O8 nanosheet
CN112337457A
Preparation method and application of cobaltosic oxide / niobate composite material with p-n junction
CN115400794A